The Problem Solver's Creative Strategy: The Role of Song and Surprise Media in Conflict Resolution - Mujiarti , Tini; Indriyani, Jiphie Gilia (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study analyzes the creative conflict resolution strategies presented in the short story The Problem Solver by Mahvira Malva Vania. The research focuses on two main objectives: (1) the psychological factors behind the character Alysa's negative prejudice towards Lindsey, and (2) the effectiveness of the song-based intervention strategy initiated by the "The Problem Solver Team" to reconcile their relationship. Using a qualitative approach and Maria Nikolajeva's theory of children's literature, which views narrative as an interactive space for a child's psychological development, this study finds that the conflict stems from insecurity and emotional instability typical of a child's developmental stage. The conflict resolution strategy, employing a surprise song performance, proved to create a safe "narrative ecology." This approach successfully functioned as an effective tool for emotional communication, breaking down psychological defenses and triggering an organic reconciliation born from internal awareness, not external pressure. The study concludes that this short story not only represents conflict but also offers a transformative resolution model. These findings reinforce the insight into children's capacity for agency and creativity in problem-solving and offer an alternative creative approach, transcending conventional methods for educators and parents in guiding children's socio-emotional development.